The Relationship Between Creativity And Dancing Ability (International Journal of Theory and Application in Elementary and Secondary School Education, 2020)
The problem in this research is the low ability of students to dance. This can be seen from the teacher has not stimulated students in dancing and the lack of student creativity in creating dance movements. This research aims to test the significance of the relationship of creativity with the ability to dance in students' elementary school. This research is a correlational study using a quantitative approach. Data collection techniques through creative tests and dance skills test.  Analytical techniques using prerequisite analysis tests include normality testing, linearity test, and hypothesis testing using the product-moment correlation analysis with the level of significance of the analysis results by 5%. Based on the results, the study showed that there was a positive and significant relationship between creativity and the ability to dance fourth-grade students of elementary school. This is evidenced by the significance of the 0.02 (P ? 0.05), meaning there is a positive relationship between creativity and the ability to dance.